Seni Ala Sufu dalam Pendekatan Diri Kepada Tuhan dan Implikasinya dalam Psikioterapi Islam - Nuraini A. Manan (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Art is a medium for the achievement of spiritual truth, its position can be compared with philosophy. Religion, art and philosophy are among the world which allows people who regarded as the material can enter into spiritual nature or spiritual nurture. The totality of one’s self and consolidation to achieve the essence of the spiritual nature can be realized with the arts as a tool. Sufi worlds have proven how the servants of Allah SWT reach the creator through language and art activities. Al-Hallaj band al-Rabiah Adawiyah relied their live to God and explained the beautiful of ma’rifah through poetic. Likewise with Jalaludin Rumi, who enjoyed the existence of God through religious dances. Not all of us can understand the nuances of pleasure and mortality experienced by the Sufi’s, but to explore the beauty of language and meaningful religious dance, will make our souls fly to the spiritual sense. Sufi’s life was identical with the value of beauty in the art in the form full of philosophical meaning. The expressions of beauty and love are manifested in the form of Sufi poetry and dance, its aim to show how much love of Sufi to Allah SWT. In remembrance of a long and deep con- templation of the nature of the creator, the Sufis came to the place which enable them to open the veil between himself and their great creator, so that they reached the climax of human self-awareness; there was only themselves in the mortality together with their loved one.